Study on the multistage iterative rank-reduced method - GUO Yi1; ZHANG Er-yang1; SHEN Rong-jun2 (Tongxin xuebao)
On the background of joint space-time anti-jammer processing for GPS receiver,multistage Wiener filter-ing（MWF）algorithm and auxiliary vector filtering（AVF）algorithm was deeply analyzed as two typical multistage itera-tive rank-reduced method in this article and their immanent relationship was pointed out.A new algorithm was proposed which has a forward recursion on the data level and a backward iterative.Compared with MWF and AVF,the proposed algorithm has a better performance,reduces the computation complexity and selects the filter rank more easily.It suits with practical realization of joint space-time anti-jammer processing for GPS receiver.Numerical simulation demon-strates that the proposed method is effect and efficient.